Penggunaan Permainan Bakiak Dalam Meningkatkan Motorik Kasar Kelompok B TK Mutiara Kecamatan Siak Hulu Kabupaten Kampar - Tryana, Nofita; Inmaryanto, Inmaryanto; Sari, Meiliza (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2022)
This research was conducted in two cycles and each cycle was conducted in two meetings. In order to ensure the research run well, the researcher arranges the stages that are passed in classroom action research, : 1) Action planning/preparation, 2) Action implementation, 3) Observation, and 4) Reflection. The subjects in this study were 14 students of B1 class consist of 8 girls and 6 boys in the first semester of the 2021/2022 academic year at TK Mutiara, Siak Hulu, Kampar.Meanwhile , the object of this research was the use of clogs game to improve gross motor skills of early childhood students . The research data were collected through teacher observation techniques and early childhood student's activities and documentation. After the data was collected through observation, the data was processed using the percentage formula. The results of this study are there is an increasing in the learning process which carried out by teachers and early childhood student's gross motor skills. Observation of children's activities also increased, It reveled from the initial data to cycle II meeting 2. Initial data was 43.83%, Cycle II meeting 2 obtained 86.36%. So that the overall increase in early childhood student's gross motor activity is 42.53%